Hemiberlesia lataniae (Signoret, 1869) (Hemiptera: Diaspididae) in Piper species (Piperaceae) in state of Pará, Brazil - Noronha, Aloyséia C. S.; Vera R. S. Wolff; Ilmarina C. Menezes; Regiane C. Vieira; Leonardo S. Duarte; Magali B. Oliveira (Entomological Communications, 2023)
We report the occurrence of scale insect Hemiberlesia lataniae (Signoret, 1869) (Hemiptera: Diaspididae) in two Piper species (Piperaceae). Hemiberlesia lataniae specimens were collected from leaves and stems of Piper cernuum Vell. and Piper reticulatum L., in a greenhouse, in the city of Belém, state of Pará. The species is reported for the first time within Piper species in Brazil.